Ultra small few layer MoS2 embedded into three-dimensional macro-micro-mesoporous carbon as a high performance lithium ion batteries anode with superior lithium storage capacity. (10th September 2019) - Huang, Moujie; Chen, Huanhui; He, Jiao; An, Bohan; Sun, Lingna; Li, Yongliang; Ren, Xiangzhong; Deng, Libo; Zhang, Peixin
Abstract: Molybdenum disulfide (MoS2 ) exhibits additional reversible capacity beyond their theoretical value is promising candidates for electrodes of lithium ion batteries (LIBs). However, the sluggish kinetics, low conductivity and self-aggregating of MoS2 nanosheets hinder the practical application. Herein, ultra small few layer MoS2 combined with carbon hybrids of macro-micro-mesoporous structure (MoS2 /MmC) is prepared via a simple and scalable liquid-solid-gas three-phase interface self-assembly process. When employed as anode for lithium ion batteries, such a clever structure possesses superior performance: exhibits discharge capacity of 938 mAh g −1 at current density of 200 mA g −1 following 100 cycles, and reveals reversible capacity of 843 mAh g −1 at current density of 2 A g −1 after 1000 cycles. The excellent performance is attributed to the rational design of electrode structure: ultra small few layer MoS2 nanosheets offer abundant active sites, while the 3D porous architectures are in favor of enhancing the mass-transportation and alleviating the volume expansion. These structural features greatly enhance surface reaction kinetics and facilitate the charge transport. Furthermore, Ex-situ XRD, FESEM are used to confirm the phase transformation of MoS2 /MmC and verify the structure stability during the cycling. It is believed that our work opens up a new possible route for the industrial production of MoS2 based anode materials. Graphical abstract: Ultra small few layer MoS2 combined with carbon hybrids of macro-micro-mesoporous structure (MoS2/MmC) is prepared via a simple and scalable liquid-solid-gas three-phase interface self-assembly process. When employed as anode for lithium ion batteries, such a clever structure possesses superior performance: exhibits discharge capacity of 938 mAh g-1 at current density of 200 mA g-1 following 100 cycles, and reveals reversible capacity of 843 mAh g-1 at current density of 2 A g-1 after 1000 cycles.Image 1 Highlights: Ultra small few layer MoS2 had been synthesized by a simple and scalable method. Abundant active sites of MoS2 /MmC derived from rich edges can enhance lithium storage capacity. The feature of MoS2 /MmC combine with MoS2 nanosheets and macro-micro-mesoporous carbon boosting the LIBs performance. Ex-situ XRD was used to explore the essence of the excellent electrochemical properties. We conceived the structural transformation mechanism of MoS2 /MmC.